2022
DOI: 10.3389/fimmu.2022.1033904
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cells: More than just immune cells

Abstract: Since their discovery, innate lymphoid cells (ILCs) have been described as the innate counterpart of the T cells. Indeed, ILCs and T cells share many features including their common progenitors, transcriptional regulation, and effector cytokine secretion. Several studies have shown complementary and redundant roles for ILCs and T cells, leaving open questions regarding why these cells would have been evolutionarily conserved. It has become apparent in the last decade that ILCs, and rare immune cells more gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 113 publications
(156 reference statements)
0
17
0
Order By: Relevance
“…Similarly, innate lymphoid cells (ILCs) have been identified in both the murine ( 11 , 25 , 26 ) and human decidua ( 8 , 27 , 28 ) and have been associated with pre-term birth ( 29 , 30 ). Although ILCs are found in circulation, they are most abundant at mucosal sites ( 31 , 32 ). And, like NK cells, many novel subsets have been identified in the decidua ( 33 , 34 ), however, questions remain as to whether they are recruited from the circulation or whether they proliferate and differentiate in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, innate lymphoid cells (ILCs) have been identified in both the murine ( 11 , 25 , 26 ) and human decidua ( 8 , 27 , 28 ) and have been associated with pre-term birth ( 29 , 30 ). Although ILCs are found in circulation, they are most abundant at mucosal sites ( 31 , 32 ). And, like NK cells, many novel subsets have been identified in the decidua ( 33 , 34 ), however, questions remain as to whether they are recruited from the circulation or whether they proliferate and differentiate in situ.…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that TRPM8 expressed in dermis was partially responsible for the activation of skin-resident ILC2s,and TRPM8,which is expressed in epidermal keratinocytes, may also be involved in sensing ambient temperature to promote local ILC2s activation ( 31 ). ILC2s express the transcription factors GATA 3 and RORα during development which are capable of producing type 2 cytokines such as IL-4,IL-5,and IL-13 ( 31 , 34 ). Stimulated by interleukin-4 (IL-4) or interleukin-13 (IL-13), keratinocytes can secrete SCCA1 and SCCA2 ( 17 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…For one, they can develop in the absence of the RAGs, RAG1 and RAG2, and express either nonrearranged or minimally rearranged transcripts for TCR chains, suggesting a potential shared origin from IL7R + lymphoid primed multipotent progenitors that fail to undergo or attempt abortive thymic T-cell selection ( 16 ). In contrast to myeloid cells, ILCs rarely rely on pattern recognition through the TLR and NOD-like receptor families ( 25 , 26 ), instead sensing tissue perturbation through both “canonical” cytokine signals and a bevy of noncanonical (nonpeptide) signals such as neurotransmitters, lipids, dietary metabolites, and other small molecules ( 2 , 3 ). An overview of this array of sensed ILC environmental inputs is provided in Fig.…”
Section: Sensing Perturbation and Danger Signalsmentioning
confidence: 99%
“…However, there is now increasing appreciation for homeostatic functions for ILCs in maintaining tissue integrity and shaping host responses well after acute perturbation ( 3 ). Thus, ILCs have a balanced, advisory role as a homeostatic “Horatio”: integrating diverse environmental cues to engage appropriate repair pathways and mitigate excessive tissue injury.…”
Section: Introductionmentioning
confidence: 99%